Support for designing waste sorting systems: A mini review. Issue 11 (November 2017) - Rousta, Kamran; Ordoñez, Isabel; Bolton, Kim; Dahlén, Lisa
This article presents a mini review of research aimed at understanding material recovery from municipal solid waste. It focuses on two areas, waste sorting behaviour and collection systems, so that research on the link between these areas could be identified and evaluated. The main results presented and the methods used in the articles are categorised and appraised. The mini review reveals that most of the work that offered design guidelines for waste management systems was based on optimising technical aspects only. In contrast, most of the work that focused on user involvement did not consider developing the technical aspects of the system, but was limited to studies of user behaviour. The only clear consensus among the articles that link user involvement with the technical system is that convenient waste collection infrastructure is crucial for supporting source separation. This mini review reveals that even though the connection between sorting behaviour and technical infrastructure has been explored and described in some articles, there is still a gap when using this knowledge to design waste sorting systems. Future research in this field would benefit from being multidisciplinary and from using complementary methods, so that holistic solutions for material recirculation can be identified. It would be beneficial to actively involve users when developing sorting infrastructures, to be sure to provide a waste management system that will be properly used by them.